0167 Teaching pop-ups: A dynamic response to participant's learning needs identified through in situ simulation. (2nd November 2015) - Trippick, Sarah; Buckley, Anna; Combes, Julie; Mackenney, Jonathan; Mak, Matthew; McEnteggart, Brian
Abstract : Background: As with many UK Emergency Departments, we have a high turnover of medical and nursing staff. 1 Consistently addressing the learning needs of this workforce is challenging, yet essential in improving patient safety, outcomes and experience. 2 Interprofessional simulation fosters a collaborative approach to needs assessment and setting common goals. 3 In situ simulated emergency medicine scenarios highlighted themes around the learning needs for the team. These themes were used to develop a series of ED shop floor teaching sessions (Pop-Ups). Methodology: A training needs-assessment survey and patient safety questionnaire was circulated to all ED staff. A multidisciplinary faculty was established to deliver a program of fortnightly in-situ simulations in-line with the responses. Scenarios were based in the resuscitation room involving a multidisciplinary team, followed by a debrief, structured around the description, analysis and application (DAA) format. 4 During the scenario a faculty member noted any observed latent safety threats on a template adapted from the NPSA contributory factors framework. 5 Concurrently, noting any learning needs around equipment, preparation of medications and the working environment. Following debrief participants were asked to complete an evaluation questionnaire. Outcomes: 25 ED staff responded to the simulation needs assessment survey. Simulations over a 5 month period show a spread of participation across the team: 48% junior doctors, 31% nursing staff, 15% registrars and 6% health-care assistants. Observed latent safety threats demonstrate the contribution of education and training factors (17%) and equipment skills (14%). Combined with the training needs assessment survey themes emerged to identify key clinical skills, scenarios and equipment requiring further training. These themes were used to form the focus and priorities for a series of evaluated ED shop floor teaching sessions. Impact: Interprofessional in situ simulation is an important tool to identify the learning needs of the team. References: Emergency Medicine taskforce – Royal College of Emergency Medicine, 2012 A framework for technology enhanced learning, DOH, 2011 Failla, et al . Interprofessional simulation: a concept analysis. Clin Simulat Nurs 2014 Courtesy of SaIL, Guys and St Thomas's Root cause analysis investigation tools. Contributory factors classification framework. National Patient Safety Agency, 2009